2010
DOI: 10.1007/s11426-010-0004-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-responsive stick-slip behavior of advancing water contact angle on the surfaces of poly(N-isopropylacrylamide)-grafted polypropylene membranes

Abstract: Wettability of a solid surface is highly important to its practical application, especially for the surface that shows thermoresponsive properties. In this paper, we describe a thermo-responsive stick-slip behavior of water droplets on the surfaces of poly(N-isopropylacrylamide) (PNIPAM)-grafted polypropylene membranes. Field emission scanning electron microscope (FESEM) images elucidate that the morphology of PNIPAM-grafted membrane surface is thermo-responsive, i.e., the surface becomes rougher above the low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 39 publications
4
19
0
Order By: Relevance
“…Applying a combined direct demodulation and deprojection technique to subtract the effects of PSF, Wang et al (2010) found that the central electron density increases by 30%, while the temperature profile is similar to the result using only a deprojection method. They also estimated that the effects of PSF were not important for the temperature profile.…”
Section: Psf Scattermentioning
confidence: 75%
See 2 more Smart Citations
“…Applying a combined direct demodulation and deprojection technique to subtract the effects of PSF, Wang et al (2010) found that the central electron density increases by 30%, while the temperature profile is similar to the result using only a deprojection method. They also estimated that the effects of PSF were not important for the temperature profile.…”
Section: Psf Scattermentioning
confidence: 75%
“…After deprojection and PSF correction (Wang et al 2010), the temperature and total mass of Abell 1835 resulting from Chandra are still different from those of XMM-Newton. These differences may result from the calibration of the two instruments.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As a result, the measured Δθ A for the different ratio films, after rinsing by cold water, were ≥ 90° at 40°C. It is important to note that in literature [11, 28], contact angles on pNIPAAm brushes and coated films were reported to have discrepancy. More importantly, pNIPAAm films exhibited a stick-slip behavior above the LCST where water contact angles reached to a value as high as 111° [28] and reduced to 92° after few stick-slip cycles.…”
Section: Resultsmentioning
confidence: 99%
“…34 This phenomenon has been explained by the theory of a "two-component system," which basically implicates a molecular-thermal inhomogeneity in the brush structure. 35 According to the theory, the temperature differences between the very top and the bottom of the brush layer might cause certain changes in motility of polymeric chains, as well as in the dynamics of water and vapor penetration inside the brush.…”
Section: Resultsmentioning
confidence: 99%